2017
DOI: 10.1038/s41598-017-00104-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel CCR2 antagonist inhibits atherogenesis in apoE deficient mice by achieving high receptor occupancy

Abstract: CC Chemokine Receptor 2 (CCR2) and its endogenous ligand CCL2 are involved in a number of diseases, including atherosclerosis. Several CCR2 antagonists have been developed as potential therapeutic agents, however their in vivo clinical efficacy was limited. In this report, we aimed to determine whether 15a, an antagonist with a long residence time on the human CCR2, is effective in inhibiting the development of atherosclerosis in a mouse disease model. First, radioligand binding assays were performed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 46 publications
(66 reference statements)
6
49
0
Order By: Relevance
“…Furthermore, proinflammatory activation and CCR2 have been implicated in acute and chronic kidney disease (9,40,41) and cardiovascular disease (6,42,43), underlining the relevance of our findings for kidney and cardiovascular patients. Patients with chronic kidney disease show increased arterial inflammation and increased proinflammatory phenotype of monocytes, as displayed by increased CCR7 and CCR2 expression (9).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, proinflammatory activation and CCR2 have been implicated in acute and chronic kidney disease (9,40,41) and cardiovascular disease (6,42,43), underlining the relevance of our findings for kidney and cardiovascular patients. Patients with chronic kidney disease show increased arterial inflammation and increased proinflammatory phenotype of monocytes, as displayed by increased CCR7 and CCR2 expression (9).…”
Section: Discussionsupporting
confidence: 54%
“…6). Among others, anti-CCR2 and the absence of CCR2 reduce atherosclerosis in mice prone for atherosclerosis development (42,43). Taken together, our data may provide a link between salt and its deleterious outcomes, which is relevant for the healthy population, as well as for patients with cardiovascular and kidney disease.…”
Section: Discussionsupporting
confidence: 52%
“…Both diabetes and vascular disease are metabolic disorders. Of note, LKB1 is a metabolic sensor and CCL2 signaling has been implicated in diabetic kidneys and vascular disease (Sayyed et al , ; Bot et al , ). This raises the possibility that in metabolic disease, the ciliary LKB1 module could confer an inflammatory phenotype on renal epithelial cells to mediate chronic inflammation in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…This trial, although also presenting negative interactions involving infection as a result of immunosuppression, highlights the potential of macrophage and inflammatory targeted treatments in the resolution of cardiovascular disease. Additional studies have demonstrated that, similarly to their role in MI, CCR2 + macrophages might also be detrimental in the case of atherosclerosis, further accentuating the potential of targeting CCR2 in predicting outcomes and developing treatments [125,126], although this warrants further investigation.…”
Section: Conflicting Roles Of Macrophage Populations In Amdmentioning
confidence: 99%